Regulation of transthyretin by thyroid hormones in Wsh - Morgado, Isabel (2014)
Transthyretin (TTR) is a thyroid hormone-binding protein (THBP) which in its tetrameric form transports thyroid hormones (THs), thyroxine (T4) and triiodothyronine (T3) in the blood of vertebrates. The principal site of production of TTR is the liver but in the sea bream TTR mRNA is also present in the heart, intestine and brain. The regulation of TTR is unstudied in Wsh and the normal circulating level of this THBP is unknown. The aim of the present study was to establish factors which regulate TTR production in Wsh. As a Wrst step a number of tools were generated; sea bream recombinant TTR (sbrTTR) and speciWc sbrTTR antisera which were used to establish an ELISA (enzyme-linked immunosorbent assay) for measuring TTR plasma levels. Subsequently, an experiment was conducted to determine the inXuence of THs on TTR production. Circulating physiological levels of TTR in sea bream determined by ELISA are approximately 3.8 gml¡1. Administration of T3 and T4 to sea bream signiWcantly increased (p< 0.001 and p<0.005, respectively) the concentration of circulating TTR (V11.5 gml¡1) in relation to control Wsh, but did not change gene transcription in the liver. Methimazol (MMI) an antithyroid agent, failed to signiWcantly reduce circulating THs below control levels but signiWcantly increased (p < 0.005) plasma TTR levels (approximately 10.8 gml¡1) and decreased (p< 0.05) transcription in the liver. Future studies will aim to elucidate in more detail these regulatory pathways.